2020
DOI: 10.1016/j.compbiomed.2020.103792
|View full text |Cite
|
Sign up to set email alerts
|

Automated detection of COVID-19 cases using deep neural networks with X-ray images

Abstract: , spread rapidly around the world and became a pandemic. It has caused a devastating effect on both daily lives, public health, and the global economy. It is critical to detect the positive cases as early as possible so as to prevent the further spread of this epidemic and to quickly treat affected patients. The need for auxiliary diagnostic tools has increased as there are no accurate automated toolkits available. Recent findings obtained using radiology imaging techniques suggest that such images contain sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
2,031
2
35

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,260 publications
(2,075 citation statements)
references
References 51 publications
7
2,031
2
35
Order By: Relevance
“…Risk factors for silent hypoxemia are old age and having diabetes [9]. Therefore, early detection of silent hypoxemia such as using prehospital pulse oximetry [5], or radiology imaging [16,17] might be used as a red ag sign of impending danger of eminent cardiac arrest or sudden respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for silent hypoxemia are old age and having diabetes [9]. Therefore, early detection of silent hypoxemia such as using prehospital pulse oximetry [5], or radiology imaging [16,17] might be used as a red ag sign of impending danger of eminent cardiac arrest or sudden respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…The overall accuracy was 89.6% while average accuracy of detecting COVID-19 was 96.6%. To test the stability and robustness, CoroNet was evaluated on the dataset prepared by Ozturk et al 13 with an accuracy of 90%. 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Ozturk et al developed DarkNet model based on the you only look once (YOLO) system to detect and classify COVID-1913 . Their model achieved the accuracy of 98.08% for classifying COVID-19 and noninfections and 87.02% for distinguish COVID-19 from COVID-19, no-ndings and GP.…”
mentioning
confidence: 99%
“…Their model achieved good accuracy for classifying two classes and three classes, respectively. Tulin et al [19] suggested in their study, the (DarkNet) Model as a classifier. This model, they used 17 convolutional layers with different filtering.…”
Section: Introductionmentioning
confidence: 99%